2009
DOI: 10.4162/nrp.2009.3.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium increases ferroportin-1 gene expression in J774 macrophage cells via the production of reactive oxygen species

Abstract: Cadmium intoxication has been associated with the dysregulation of iron homeostasis. In the present study, we investigated the effect of cadmium on the expression of ferroportin 1 (FPN1), an important iron transporter protein that is involved in iron release from macrophages. When we incubated cadmium with J774 mouse macrophage cells, FPN1 mRNA levels were significantly increased in a dose- and time-dependent manner. Furthermore, the cadmium-induced FPN1 mRNA expression was associated with increased levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Recently, it was shown that cadmium induction of FPN1 transcription was dependent on the generation of oxidative radicals. 29 This observation is consistent with our data and with the established role of cadmium in induction of MTF-1 responsive genes. Cadmium can directly displace zinc from metallothionein or damage metallothionein by generating oxidative radicals that would act on metallothionein and release zinc.…”
supporting
confidence: 82%
“…Recently, it was shown that cadmium induction of FPN1 transcription was dependent on the generation of oxidative radicals. 29 This observation is consistent with our data and with the established role of cadmium in induction of MTF-1 responsive genes. Cadmium can directly displace zinc from metallothionein or damage metallothionein by generating oxidative radicals that would act on metallothionein and release zinc.…”
supporting
confidence: 82%
“…In macrophages, hemoglobin (Hb) is degraded and the iron released is exported into plasma through ferroportin1 on the membrane. During the process, Cd increases ferroportin1 expression in mouse macrophages (Park and Chung, 2009).…”
mentioning
confidence: 99%
“…In the cell, iron is reduced to the ferric form and exported to the blood by ferroportin 1 [solute carrier family 40 (iron-regulated transporter), member 1; SLC40A1, formerly FPN1 ] at the basolateral membrane. Troadec et al (2010) reported a role for FPN1 in transition metal efflux (Cd and Zn) in mouse bone marrow macrophages, and Park and Chung (2009) found that Cd exposure increased FPN1 expression in macrophages. In blood, iron is bound to mobile transferrin ( TF ) and ferritin.…”
mentioning
confidence: 99%